2022
DOI: 10.1038/s41379-021-00928-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence suggests that cutaneous neuroendocrine carcinomas can arise from squamous dysplastic precursors

Abstract: Merkel cell carcinoma (MCC) is an aggressive cutaneous neuroendocrine carcinoma without a known dysplastic precursor. In some cases, MCC is associated with SCCIS in the overlying epidermis; however, the MCC and SCCIS populations display strikingly different morphologies, and thus far a relationship between these components has not been demonstrated. To better understand the relationship between these distinct tumor cell populations, we evaluated 7 pairs of MCC-SCCIS for overlapping genomic alterations by cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 59 publications
6
30
0
Order By: Relevance
“…These may seem to be contradictory because H3K27me3 is associated with closed chromatin and transcriptional repression, whereas H3K27ac is associated with open chromatin. However, the comparisons made were not identical, and Harms et al (2021) rightly posit that MCC-associated SCCIS components represent a minority subset of RB1-inactivated SCCIS. They are thus unusually permissive for a neuroendocrine switch, occupying an intermediate unique genetic and epigenetic state between typical cutaneous SCCIS or SCC and UV-induced MCC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These may seem to be contradictory because H3K27me3 is associated with closed chromatin and transcriptional repression, whereas H3K27ac is associated with open chromatin. However, the comparisons made were not identical, and Harms et al (2021) rightly posit that MCC-associated SCCIS components represent a minority subset of RB1-inactivated SCCIS. They are thus unusually permissive for a neuroendocrine switch, occupying an intermediate unique genetic and epigenetic state between typical cutaneous SCCIS or SCC and UV-induced MCC.…”
Section: Discussionmentioning
confidence: 92%
“…First, on the basis of the mutational profiles and greater number of mutations in MCC than in SCCIS, MCPyV-negative MCC can arise from SCCIS. Second, although no mutational event clearly appears to be required for the MCC transition, RB1 inactivation is likely obligate, especially given the additional decrease in expression in the MCC component noted by Harms et al (2021) H3K27me1 and H3K27ac levels. These may seem to be contradictory because H3K27me3 is associated with closed chromatin and transcriptional repression, whereas H3K27ac is associated with open chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…For assessing the impact of and to establish the research directions for squamous cell carcinomas, we used the scientometric method [ 3 , 4 ]. A set of instructions was defined based on the keywords from the 76 articles we assessed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the loss of the repressive H3K27me3 mark was observed in all components, which is a recently described determinant of MCPyV-negative MCC development. 5 The MCPyV sequence was not detected by qPCR. 7 After dissection by needle sampling 6 of the three components in case #1 and of the MCC and sarcomatoid components in case #2, MPS using a panel of 93 cancer-related genes confirmed the presence of two shared pathogenic variants in the three components in case #1 and of five shared pathogenic variants in the two available components in case #2 (Table 1).…”
Section: Genetic Evidence Of a Sarcomatoid Transformation In Merkel C...mentioning
confidence: 99%
“…4 Recently, applying massive parallel sequencing (MPS) to paired MCC and in situ SCC cases, we and others have shown that in combined tumours, MCC derived from SCC, thus demonstrating the keratinocytic origin of these cases. 5,6 Beyond SCC, several differentiation lineages have been observed in association with MCC. 4 Among these, combined MCC with a sarcomatoid component was rarely reported (13 cases).…”
Section: Genetic Evidence Of a Sarcomatoid Transformation In Merkel C...mentioning
confidence: 99%